Improved Laser Manipulation for On-chip Fabricated Microstructures Based on Solution Replacement and Its Application in Single Cell Analysis. (6th February 2014) - Yue, Tao; Nakajima, Masahiro; Takeuchi, Masaru; Fukuda, Toshio
In this paper, we present the fabrication and assembly of microstructures inside a microfluidic device based on a photocrosslinkable resin and optical tweezers. We also report a method of solution replacement inside the microfluidic channel in order to improve the manipulation performance and apply the assembled microstructures for single cell cultivation. By the illumination of patterned ultraviolet (UV) through a microscope, microstructures of arbitrary shape were fabricated by the photocrosslinkable resin inside a microfluidic channel. Based on the microfluidic channel with both glass and polydimethylsiloxane (PDMS) surfaces, immovable and movable microstructures were fabricated and manipulated. The microstructures were fabricated at the desired places and manipulated by the optical tweezers. A rotational microstructure including a microgear and a rotation axis was assembled and rotated in demonstrating this technique. The improved laser manipulation of microstructures was achieved based on the on-chip solution replacement method. The manipulation speed of the microstructures increased when the viscosity of the solvent decreased. The movement efficiency of the fabricated microstructures inside the lower viscosity solvent was evaluated and compared with those microstructures inside the former high viscosity solvent. A novel cell cage was fabricated and the cultivation of a single yeast cell ( w303 ) was demonstrated in the cell cage, inside the microfluidic device.